Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery
Patent Information
- Application Number
- CN202311622884.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-29
AI Technical Summary
[0003]在离子掺杂中,各种阳离子和阴离子作为掺杂剂在磷酸铁锂正极材料中的应用已被广泛研究,且这些大多是离子掺杂,通过在晶体结构中占据特殊位点,来提高导电性,而针对磷酸铁锂正极材料表面的碳层进行杂原子修饰掺杂的研究则不多
[0047] In the preparation method of lithium iron phosphate cathode material of this application, boron and/or fluorine elements are added during the preparation process of lithium iron phosphate, so that the bulk phase of the prepared lithium iron phosphate cathode material is doped with boron/fluorine elements, or fluorine elements are doped in the carbon coating layer on the surface. Using polyvinylidene fluoride (PVDF) as a specific fluorine source to modify lithium iron phosphate results in fluorine-doped lithium iron phosphate cathode materials with excellent electrochemical performance and high rate performance. If fluorine is doped in the bulk phase, fluoride ions prefer specific oxygen sites in the crystal structure, which can enhance the conductivity of the material and retain the olivine structure of LiFePO4 after doping. Simultaneously, the lattice parameters and antisite defects are reduced, and the crystal size is increased, which has a positive impact on electrochemical performance. If fluorine is doped in the carbon coating layer, using PVDF as the carbon source results in an fluorine-doped carbon coating layer with a lower charging potential and a higher discharging potential, thus reducing the difference between charge and discharge potential. Furthermore, the introduction of fluorine fluorinates the olivine-type phosphate, forming a uniform, highly conductive carbon coating that enhances the electrochemical characteristics of the LiFePO4-based material. Doping with boron sources can increase the powder compaction density of lithium iron phosphate cathode materials, resulting in smaller polarization, higher capacity, and longer cycle life, thereby improving electrochemical performance.
Smart Images

Figure CN117720113B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, and in particular to a lithium iron phosphate cathode material, its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium iron phosphate (LiFePO4) with an olivine structure is a commonly used cathode material. Its main characteristics include high energy density (578 Wh / kg, theoretical capacity 170 mAh / g, plateau voltage 3.4 V vs. LiFePO4). + The material boasts advantages such as structural stability, low cost, and environmental compatibility. However, despite these advantages, it suffers from low intrinsic electronic conductivity and low lithium-ion diffusion rate, which have become obstacles limiting its applications. Currently, three common methods are used to overcome this obstacle: (i) preparing composite materials with conductive additives; (ii) minimizing particle size; and (iii) ion doping.
[0003] In ion doping, the application of various cations and anions as dopants in lithium iron phosphate cathode materials has been extensively studied, and most of these are ion doping methods that improve conductivity by occupying specific sites in the crystal structure. However, research on heteroatom modification and doping of the carbon layer on the surface of lithium iron phosphate cathode materials is limited. Therefore, providing a new preparation method to prepare doped lithium iron phosphate cathode materials and improve their electrochemical performance is of significant research importance. Summary of the Invention
[0004] The purpose of this application is to provide a lithium iron phosphate cathode material, a method for preparing the same, and a lithium-ion battery. The method involves preparing a boron- and / or fluorine-doped lithium iron phosphate cathode material by using a special boron source and / or fluorine source.
[0005] To achieve the above objectives, the technical solution of this application is as follows:
[0006] In a first aspect, this application provides a method for preparing a lithium iron phosphate cathode material, comprising:
[0007] Raw materials including iron, phosphorus, lithium and carbon sources are dissolved in a solvent, and after the solvent is evaporated, a precursor material is obtained.
[0008] The precursor material is subjected to a first sintering and a second sintering to obtain the lithium iron phosphate cathode material.
[0009] The lithium iron phosphate cathode material is doped with boron and / or fluorine;
[0010] When the lithium iron phosphate cathode material is doped with boron, the raw material also includes a boron source;
[0011] When the lithium iron phosphate cathode material is doped with fluorine, the carbon source includes polyvinylidene fluoride (PVDF), and / or, the precursor material is mixed with the fluorine source before the first sintering.
[0012] Optionally, the preparation method of the lithium iron phosphate cathode material satisfies at least one of the following conditions:
[0013] a. The iron source includes at least one of ferrous oxalate, ferrous acetate, ferrous chloride, ferrous sulfate, ferric oxide, ferric phosphate, ferric nitrate, ferric chloride, ferric sulfate, ferric hydroxide, ferric citrate, and ferric acetate;
[0014] b. The phosphorus source includes at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, iron phosphate, lithium phosphate, and lithium dihydrogen phosphate;
[0015] c. The lithium source includes at least one of lithium hydroxide, lithium oxalate, lithium carbonate, lithium acetate, lithium phosphate, lithium dihydrogen phosphate, lithium hydrogen phosphate, lithium chloride, and lithium nitrate;
[0016] d. The carbon source includes at least one of glucose, sucrose, starch, citric acid, amino acids, polyethylene glycol, and polyvinylidene fluoride;
[0017] e. The solvent includes at least one of water and a hydrophilic organic solvent;
[0018] f. The boron source includes at least one selected from boron oxide, boron phosphate, trimethyl borate, triethyl borate, and tripropyl borate;
[0019] g. The fluorine source is polyvinylidene fluoride (PVDF).
[0020] Optionally, the preparation method of the lithium iron phosphate cathode material satisfies at least one of the following conditions:
[0021] h. The molar ratio of iron, phosphorus, and lithium in the iron source, phosphorus source, and lithium source is (0.90-1.15):(0.95-1.15):(0.95-1.15);
[0022] i. The mass of the carbon source is 1%-20% of the theoretical yield of the lithium iron phosphate cathode material;
[0023] j. The mass of the boron source does not exceed 5% of the theoretical yield of the lithium iron phosphate cathode material;
[0024] k. The mass of the fluorine source is 0-10% of the theoretical yield of the lithium iron phosphate cathode material.
[0025] Optionally, the method for preparing the lithium iron phosphate cathode material further satisfies at least one of the following conditions:
[0026] l. The step of mixing the precursor material with the fluorine source includes: dissolving the fluorine source in N-methyl-2-pyrrolidone (NMP), then adding the precursor material, mixing, and drying.
[0027] m. The first sintering includes: in an inert gas atmosphere, heating from room temperature to 100℃-380℃, holding at that temperature for 1h-1.5h, then further heating to 480℃-680℃, holding at that temperature for 4.5h-6.5h, and then cooling to room temperature;
[0028] n. The second sintering process includes: heating from room temperature to 480℃-680℃ in an inert gas atmosphere, holding at that temperature for 1h-1.5h, then further heating to 680℃-810℃, holding at that temperature for 4.5h-8h, and then cooling to room temperature;
[0029] o. The raw material also includes polymer monomers.
[0030] Preferably, the preparation method further satisfies at least one of the following conditions:
[0031] p. The heating rates of the first sintering and the second sintering are each independently 1℃ / min-5℃ / min;
[0032] q. The drying process includes: vacuum drying at 100℃-150℃;
[0033] r. The polymer monomer includes at least one of styrene, propylene, acrylic acid, acrylate, acrylamide, acrylonitrile and their derivatives;
[0034] s. The molar amount of the polymer monomer is 1.1%-220% of the molar amount of iron in the iron source.
[0035] Preferably, when the raw material further comprises a polymer monomer, dissolving the raw material in a solvent includes:
[0036] The raw materials, including an iron source, a phosphorus source, a lithium source, and the polymer monomer, are dissolved in the solvent containing an oxidizing acid and / or a non-oxidizing acid to obtain a mixture.
[0037] When the mixture contains the oxidizing acid, the carbon source is added to the mixture to allow the solvent to evaporate naturally and the polymer monomers to undergo a polymerization reaction to generate a polymer.
[0038] When the mixture does not contain the oxidizing acid, the carbon source is added to the mixture, followed by the addition of hydrogen peroxide to allow the solvent to evaporate naturally and the polymer monomers to undergo a polymerization reaction to generate a polymer.
[0039] More preferably, the preparation method satisfies at least one of the following conditions:
[0040] The oxidizing acid includes at least one of nitric acid and sulfuric acid;
[0041] u. The non-oxidizing acid includes at least one of hydrochloric acid, phosphoric acid, and acetic acid;
[0042] v. The hydrogen ion concentration in the mixture is above 1 mol / L.
[0043] Optionally, before performing the first sintering and the second sintering, the process further includes: refining the particle size of the precursor material.
[0044] Secondly, this application provides a lithium iron phosphate cathode material, which is prepared using the method for preparing lithium iron phosphate cathode materials described in the first aspect.
[0045] Thirdly, this application provides a lithium-ion battery, including the lithium iron phosphate cathode material described in the second aspect.
[0046] The beneficial effects of this application are:
[0047] In the preparation method of lithium iron phosphate cathode material of this application, boron and / or fluorine elements are added during the preparation process of lithium iron phosphate, so that the bulk phase of the prepared lithium iron phosphate cathode material is doped with boron / fluorine elements, or fluorine elements are doped in the carbon coating layer on the surface. Using polyvinylidene fluoride (PVDF) as a specific fluorine source to modify lithium iron phosphate results in fluorine-doped lithium iron phosphate cathode materials with excellent electrochemical performance and high rate performance. If fluorine is doped in the bulk phase, fluoride ions prefer specific oxygen sites in the crystal structure, which can enhance the conductivity of the material and retain the olivine structure of LiFePO4 after doping. Simultaneously, the lattice parameters and antisite defects are reduced, and the crystal size is increased, which has a positive impact on electrochemical performance. If fluorine is doped in the carbon coating layer, using PVDF as the carbon source results in an fluorine-doped carbon coating layer with a lower charging potential and a higher discharging potential, thus reducing the difference between charge and discharge potential. Furthermore, the introduction of fluorine fluorinates the olivine-type phosphate, forming a uniform, highly conductive carbon coating that enhances the electrochemical characteristics of the LiFePO4-based material. Doping with boron sources can increase the powder compaction density of lithium iron phosphate cathode materials, resulting in smaller polarization, higher capacity, and longer cycle life, thereby improving electrochemical performance.
[0048] The lithium iron phosphate cathode material of this application improves the electrochemical performance of the cathode material through boron and / or fluorine doping. Attached Figure Description
[0049] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0050] Figure 1 SEM image of the lithium iron phosphate cathode material prepared in Example 1;
[0051] Figure 2 The particle size distribution diagram is shown for the lithium iron phosphate cathode material prepared in Example 1.
[0052] Figure 3 SEM image of the lithium iron phosphate cathode material prepared in Example 3;
[0053] Figure 4 This is a particle size distribution diagram of the lithium iron phosphate cathode material prepared in Example 3. Detailed Implementation
[0054] As used in this article:
[0055] "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such a composition, step, method, article, or apparatus. The conjunction "composed of" excludes any unnamed elements, steps, or components.
[0056] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0057] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0058] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (K is any number representing a multiplier). It is important to understand that, unlike the number of parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0059] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0060] In a first aspect, this application provides a method for preparing a lithium iron phosphate cathode material, comprising:
[0061] S100: Dissolve the raw materials, including iron source, phosphorus source, lithium source and carbon source, in a solvent, and after the solvent is evaporated, obtain the precursor material;
[0062] S200: The precursor material is subjected to a first sintering and a second sintering to obtain the lithium iron phosphate cathode material.
[0063] In this application, the lithium iron phosphate cathode material is doped with boron and / or fluorine. More specifically, the lithium iron phosphate cathode material of this application is actually based on lithium iron phosphate, and a carbon layer is coated on the surface of the substrate. Boron / fluorine elements are doped in the bulk phase of the lithium iron phosphate cathode material, or fluorine elements are doped in the carbon coating layer on the surface, forming a boron and / or fluorine-doped lithium iron phosphate material.
[0064] When the lithium iron phosphate cathode material is doped with boron, the raw materials in S100 also include a boron source. Specifically, an iron source, a phosphorus source, a lithium source, a boron source, and a carbon source are dissolved in a solvent, and after the solvent is evaporated, a boron-containing precursor material is obtained.
[0065] In a preferred embodiment, the boron source includes at least one selected from boron oxide, boron phosphate, trimethyl borate, triethyl borate, and tripropyl borate.
[0066] In a preferred embodiment, the mass of the boron source does not exceed 5% of the theoretical yield of the lithium iron phosphate cathode material.
[0067] When lithium iron phosphate cathode material is doped with fluorine, the carbon source in S100 includes polyvinylidene fluoride, or, before the first sintering in S200, the precursor material needs to be mixed with the fluorine source.
[0068] It should be noted that polyvinylidene fluoride can be used as a carbon source to prepare precursor materials by combining it with raw materials such as iron, phosphorus, and lithium sources, and then sintering them to obtain carbon-coated lithium iron phosphate materials; it can also be used as a fluorine source to prepare fluorine-doped carbon-coated lithium iron phosphate materials.
[0069] In a preferred embodiment, the carbon source includes at least one of glucose, sucrose, starch, citric acid, amino acids, polyethylene glycol, and polyvinylidene fluoride.
[0070] When the carbon source in S100 is selected from substances such as glucose, sucrose, starch, citric acid, amino acids, and polyethylene glycol, in order to ensure that the lithium iron phosphate cathode material is doped with fluorine, the precursor material and the fluorine source need to be mixed before the first sintering.
[0071] In a preferred embodiment, the fluorine source is polyvinylidene fluoride.
[0072] In a preferred embodiment, the mass of the fluorine source is 0-10% of the theoretical yield of the lithium iron phosphate cathode material. When polyvinylidene fluoride is selected as the carbon source in the raw materials, the amount of fluorine source added can be 0.
[0073] In a preferred embodiment, the step of mixing the precursor material with the fluorine source includes: dissolving the fluorine source in N-methyl-2-pyrrolidone, then adding the precursor material, mixing, stirring evenly, and drying. Furthermore, the drying process requires vacuum drying at a temperature of 100°C-150°C to prevent reaction with substances such as oxygen or to prevent the generation of impurities.
[0074] In a preferred embodiment, the iron source in S100 includes at least one of ferrous oxalate, ferrous acetate, ferrous chloride, ferrous sulfate, ferric oxide, ferric phosphate, ferric nitrate, ferric chloride, ferric sulfate, ferric hydroxide, ferric citrate, and ferric acetate.
[0075] In a preferred embodiment, the phosphorus source in S100 includes at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, iron phosphate, lithium phosphate, and lithium dihydrogen phosphate.
[0076] In a preferred embodiment, the lithium source in S100 includes at least one of lithium hydroxide, lithium oxalate, lithium carbonate, lithium acetate, lithium phosphate, lithium dihydrogen phosphate, lithium hydrogen phosphate, lithium chloride, and lithium nitrate.
[0077] In a preferred embodiment, the solvent in S100 includes at least one of water and a hydrophilic organic solvent. Specifically, the hydrophilic organic solvent includes at least one of methanol, ethanol, propanol, isopropanol, n-butanol, acetone, butanone, and dimethyl ethyl ketone. More preferably, the solvent in S100 is water.
[0078] In a preferred embodiment, the molar ratio of iron, phosphorus, and lithium elements in the iron source, phosphorus source, and lithium source in S100 is (0.90-1.15):(0.95-1.15):(0.95-1.15), for example, it can be any value between 0.90:0.95:1, 0.95:1:1.05, 1:0.95:1.15, 1.1:1:0.95, 1.15:1.1:1, 1:1:1, or (0.90-1.15):(0.95-1.15):(0.95-1.15), more preferably 1:1:1.
[0079] In a preferred embodiment, the mass of the carbon source in S100 is 1%-20% of the theoretical yield of lithium iron phosphate cathode material. If the mass of the carbon source is too high, the resulting carbon layer thickness will also be too thick, thereby affecting the capacity and other properties of the cathode material.
[0080] In a preferred embodiment, the first sintering in S200 includes: heating from room temperature to 100℃-380℃ in an inert gas atmosphere, holding at that temperature for 1h-1.5h, then further heating to 480℃-680℃, holding at that temperature for 4.5h-6.5h, and then cooling to room temperature.
[0081] In a preferred embodiment, the second sintering in S200 includes: heating from room temperature to 480℃-680℃ in an inert gas atmosphere, holding at that temperature for 1h-1.5h, then further heating to 680℃-810℃, holding at that temperature for 4.5h-8h, and then cooling to room temperature.
[0082] More preferably, the heating rates of the first sintering and the second sintering are each independently 1℃ / min-5℃ / min, for example, the heating rates of the first sintering and the second sintering are both 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min or 5℃ / min; or the heating rates of the first sintering and the second sintering are not the same, for example, the heating rate of the first sintering is 1℃ / min and the heating rate of the second sintering is 2℃ / min; or the heating rate of the first sintering is 2℃ / min and the heating rate of the second sintering is 5℃ / min; or the heating rate of the first sintering is 5℃ / min and the heating rate of the second sintering is 3℃ / min, and so on.
[0083] In a preferred embodiment of this application, the raw material in S100 further includes polymer monomers.
[0084] More preferably, when the raw material of S100 also contains polymer monomers, dissolving the raw material in a solvent specifically includes: dissolving the raw material, which includes an iron source, a phosphorus source, a lithium source and the polymer monomers, in a solvent containing an oxidizing acid and / or a non-oxidizing acid to obtain a mixture.
[0085] When the mixture contains oxidizing acids, a carbon source is added to the mixture to allow the solvent in the mixture to evaporate naturally and to allow the polymer monomers to undergo a polymerization reaction to generate a polymer.
[0086] Specifically, the oxidizing acid includes at least one of nitric acid and sulfuric acid, which possess strong oxidizing and acidic properties. Therefore, after adding a carbon source to the mixture, the entire solution system can spontaneously generate heat, thereby promoting the polymerization reaction of the polymer monomers. After the heat released by the spontaneously generating reaction evaporates the solvent in the mixture, a solid precursor material is obtained. By using an oxidizing acid in the system with added polymer monomers and then adding a carbon source, the entire process can promote the polymerization reaction of polymer monomers without the need for external energy, such as heating, light exposure, or heating initiators, which greatly reduces the preparation cost.
[0087] When the mixture contains non-oxidizing acids instead of oxidizing acids, a carbon source is added to the mixture, followed by hydrogen peroxide to allow the solvent in the mixture to evaporate naturally and to allow the polymer monomers to polymerize and form a polymer.
[0088] Specifically, non-oxidizing acids include at least one of hydrochloric acid, phosphoric acid, and acetic acid. These acids are weak and have little oxidizing power. Therefore, it is necessary to add a strong oxidizing agent such as hydrogen peroxide to promote the exothermic reaction of the system and thus induce the polymer monomers to undergo polymerization.
[0089] After the polymerization reaction, the surface of the precursor material is actually coated with the polymer obtained from the reaction, in addition to the carbon source material. After sintering in S200, the polymer undergoes a thermal decomposition reaction to form conductive carbon, thereby preparing a lithium iron phosphate cathode material with a relatively regular morphology and reasonable particle size distribution.
[0090] In a preferred embodiment, the polymer monomer includes at least one selected from styrene, propylene, acrylic acid, acrylate, acrylamide, acrylonitrile, and their derivatives. Each of these monomers contains at least one carbon-carbon double bond to ensure that the polymerization reaction occurs.
[0091] In a preferred embodiment, the molar amount of polymer monomer is 1.1%-220% of the molar amount of iron in the iron source. Controlling the amount of polymer monomer added within a suitable range can ensure that lithium iron phosphate cathode material with appropriate particle size is obtained. If too much is added, the large amount of polymer formed by polymerization will form a gel, which will limit the nucleation / growth of the iron, phosphorus, and lithium sources. If too little is added, it is impossible to effectively improve the morphology and particle size distribution of the cathode material, and thus it is difficult to improve the compaction density of the electrode, resulting in a low battery specific capacity.
[0092] In a preferred embodiment, the hydrogen ion concentration in the mixture containing the added monomers is above 1 mol / L to ensure the acidic state of the mixture. This facilitates better redox reactions between the oxidizing acid and the carbon source, or between hydrogen peroxide and the carbon source, resulting in spontaneous exothermic reactions and promoting the opening of double bonds in the polymer monomers to generate the polymer.
[0093] In a preferred embodiment, before the first sintering and the second sintering in S200, the process further includes: refining the particle size of the precursor material.
[0094] Specifically, the particle size of the precursor material can be controlled to below 2μm through grinding, air jet milling, etc., so that the size of the material after sintering will not be too large, and the amount of material discarded as waste after sieving will be greatly reduced.
[0095] Secondly, this application also provides a lithium iron phosphate cathode material, which is prepared using the method for preparing lithium iron phosphate cathode materials described in the first aspect above.
[0096] Thirdly, this application provides a lithium-ion battery comprising the aforementioned lithium iron phosphate cathode material.
[0097] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0098] Example 1
[0099] This embodiment provides a lithium iron phosphate cathode material, specifically a boron-fluorine co-doped lithium iron phosphate cathode material, and the preparation method includes:
[0100] (1) Ferric nitrate, ammonium dihydrogen phosphate, lithium acetate, boron oxide, and PVDF were uniformly dissolved in water to obtain a mixed solution. The water was then completely evaporated to obtain a solid precursor material. The molar ratio of iron, phosphorus, and lithium in ferric nitrate, ammonium dihydrogen phosphate, and lithium acetate was 0.97:1:1. The mass of PVDF was 10% of the mass of the final lithium iron phosphate cathode material, and the mass of boron oxide was 0.3% of the mass of the final lithium iron phosphate cathode material.
[0101] (2) The solid precursor material was sintered in a nitrogen atmosphere, specifically in two stages: a first sintering stage and a second sintering stage. In the first sintering stage, the temperature was increased from room temperature to 180°C at a rate of 5°C / min and sintered for 1 hour, then increased from 180°C to 530°C at a rate of 5°C / min and sintered for 5.5 hours, followed by cooling. In the second sintering stage, the temperature was increased from room temperature to 530°C at a rate of 5°C / min and sintered for 1.5 hours, then increased from 530°C to 750°C at a rate of 5°C / min and sintered for 5.5 hours. Finally, the temperature was reduced from 750°C to room temperature at a rate of 5°C / min to obtain the boron-fluorine co-doped lithium iron phosphate cathode material.
[0102] Example 2
[0103] This embodiment provides a lithium iron phosphate cathode material, specifically a boron-fluorine co-doped lithium iron phosphate cathode material, and the preparation method includes:
[0104] (1) Ferric nitrate, ammonium dihydrogen phosphate, lithium acetate, and boron oxide are uniformly dissolved in water to obtain a first mixture. Then, a carbon source (glucose) is added, and the mixture is stirred until homogeneous to obtain a second mixture. The water in the second mixture is then completely evaporated to obtain a solid precursor material. The molar ratio of iron, phosphorus, and lithium in ferric nitrate, ammonium dihydrogen phosphate, and lithium acetate is 0.97:1:1. The mass of glucose is 5% of the final mass of the prepared lithium iron phosphate cathode material, and the mass of boron oxide is 0.3% of the final mass of the prepared lithium iron phosphate cathode material.
[0105] (2) Take PVDF (the mass of PVDF is 10% of the mass of the finished lithium iron phosphate cathode material) and dissolve it in N-methyl-2-pyrrolidone (NMP). Then mix it with the solid precursor material, dry the mixture in a vacuum drying oven at 120°C, and then grind it to obtain the powdered precursor material.
[0106] (3) The powder precursor material is sintered in a nitrogen atmosphere, specifically in two stages: a first sintering stage and a second sintering stage. In the first sintering stage, the temperature is increased from room temperature to 380°C at a rate of 5°C / min and sintered for 1.5 h, then increased from 380°C to 530°C at a rate of 5°C / min and sintered for 6.5 h, followed by cooling. In the second sintering stage, the temperature is increased from room temperature to 530°C at a rate of 5°C / min and sintered for 1.5 h, then increased from 530°C to 750°C at a rate of 5°C / min and sintered for 5.5 h. Finally, the temperature is reduced from 750°C to room temperature at a rate of 5°C / min to obtain the boron-fluorine co-doped lithium iron phosphate cathode material.
[0107] Example 3
[0108] This embodiment provides a lithium iron phosphate cathode material, specifically a boron-fluorine co-doped lithium iron phosphate cathode material, and the preparation method includes:
[0109] (1) Ferric nitrate, ammonium dihydrogen phosphate, lithium acetate, boron oxide, acrylic acid, and concentrated nitric acid are mixed and dissolved in water to obtain a first mixture. Then, a carbon source (PVDF) is added, and stirring is continued to allow the water in the first mixture to evaporate naturally and the polymer monomers to undergo a polymerization reaction to form a polymer. After the water has completely evaporated, a solid precursor material is obtained. Among them, the molar ratio of iron, phosphorus, and lithium in ferric nitrate, ammonium dihydrogen phosphate, and lithium acetate is 0.97:1:1, the molar amount of acrylic acid is 10% of the molar amount of iron in ferric acetate, the mass of PVDF is 10% of the mass of the final lithium iron phosphate cathode material, and the mass of boron oxide is 0.3% of the mass of the final lithium iron phosphate cathode material.
[0110] (2) Same as step (2) in Example 1.
[0111] Example 4
[0112] This embodiment provides a lithium iron phosphate cathode material, specifically a boron-fluorine co-doped lithium iron phosphate cathode material, and the preparation method includes:
[0113] (1) Ferric nitrate, ammonium dihydrogen phosphate, lithium acetate, boron oxide, acrylic acid, and concentrated nitric acid are mixed and dissolved in water to obtain a first mixture. Then, a carbon source (glucose) is added, and stirring is continued to allow the water in the first mixture to evaporate naturally and the polymer monomers to undergo a polymerization reaction to generate a polymer. After the water has completely evaporated, a solid precursor material is obtained. Among them, the molar ratio of iron, phosphorus, and lithium in ferric nitrate, ammonium dihydrogen phosphate, and lithium acetate is 0.97:1:1; the molar amount of acrylic acid is 10% of the molar amount of iron in ferric nitrate; the concentration of concentrated nitric acid is 63 wt%, and its molar amount is 10% of the molar amount of iron in ferric nitrate; the mass of glucose is 5% of the mass of the final lithium iron phosphate cathode material; and the mass of boron oxide is 0.3% of the mass of the final lithium iron phosphate cathode material.
[0114] (2) Same as step (2) in Example 2
[0115] (3) Same as step (3) in Example 2.
[0116] Example 5
[0117] This embodiment provides a lithium iron phosphate cathode material, prepared using the same method as in Example 4, except that:
[0118] In step (1), the molar ratio of iron, phosphorus and lithium in ferric nitrate, ammonium dihydrogen phosphate and lithium acetate is 0.99:1:1, and the mass of boron oxide is 0.1% of the mass of the final lithium iron phosphate cathode material.
[0119] In step (3), during the second sintering stage, the temperature is increased from room temperature to 530°C at a heating rate of 5°C / min and sintered for 1.5 h. Then, the temperature is increased from 530°C to 730°C at a heating rate of 5°C / min and sintered for 5.5 h. Finally, the temperature is decreased from 730°C to room temperature at a cooling rate of 5°C / min to obtain boron-fluorine co-doped lithium iron phosphate cathode material.
[0120] Example 6
[0121] This embodiment provides a lithium iron phosphate cathode material, specifically a fluorine-doped lithium iron phosphate cathode material, and the preparation method includes:
[0122] (1) Ferric nitrate, ammonium dihydrogen phosphate, lithium acetate, acrylic acid, and concentrated nitric acid are mixed and dissolved in water to obtain a first mixture. A carbon source (glucose) is then added, and stirring is continued to allow the water in the first mixture to evaporate naturally and for the polymer monomers to undergo a polymerization reaction to form a polymer. After the water has completely evaporated, a solid precursor material is obtained. The molar ratio of iron, phosphorus, and lithium in ferric nitrate, ammonium dihydrogen phosphate, and lithium acetate is 0.99:1:1. The molar amount of acrylic acid is 10% of the molar amount of iron in ferric acetate. The concentration of concentrated nitric acid is 63 wt%, and the mass of glucose is 5% of the final mass of the prepared lithium iron phosphate cathode material.
[0123] (2) Take PVDF (the mass of PVDF is 10% of the mass of the finished lithium iron phosphate cathode material) and dissolve it in N-methyl-2-pyrrolidone (NMP). Then mix it with the solid precursor material, dry the mixture in a vacuum drying oven at 120°C, and then grind it to obtain the powdered precursor material.
[0124] (3) The powder precursor material is sintered in a nitrogen atmosphere, specifically in two stages: a first sintering stage and a second sintering stage. In the first sintering stage, the temperature is increased from room temperature to 380°C at a rate of 5°C / min and sintered for 1.5 h, then increased from 380°C to 530°C at a rate of 5°C / min and sintered for 6.5 h, followed by cooling. In the second sintering stage, the temperature is increased from room temperature to 530°C at a rate of 5°C / min and sintered for 1.5 h, then increased from 530°C to 730°C at a rate of 5°C / min and sintered for 5.5 h. Finally, the temperature is reduced from 730°C to room temperature at a rate of 5°C / min to obtain fluorine-doped lithium iron phosphate cathode material.
[0125] Example 7
[0126] This embodiment provides a lithium iron phosphate cathode material, specifically a boron-doped lithium iron phosphate cathode material, and the preparation method includes:
[0127] (1) Ferric nitrate, ammonium dihydrogen phosphate, lithium acetate, boron oxide, acrylic acid, and concentrated nitric acid are mixed and dissolved in water to obtain a first mixture. Then, a carbon source (glucose) is added, and stirring is continued to allow the water in the first mixture to evaporate naturally and for the polymer monomers to undergo a polymerization reaction to generate a polymer. After the water has completely evaporated, a solid precursor material is obtained. Among them, the molar ratio of iron, phosphorus, and lithium in ferric nitrate, ammonium dihydrogen phosphate, and lithium acetate is 0.97:1:1, the molar amount of acrylic acid is 10% of the molar amount of iron in ferric nitrate, the concentration of concentrated nitric acid is 63wt%, the mass of glucose is 10% of the mass of the final lithium iron phosphate cathode material, and the mass of boron oxide is 0.3% of the mass of the final lithium iron phosphate cathode material.
[0128] (2) The solid precursor material is sintered in a nitrogen atmosphere, specifically in two stages: a first sintering stage and a second sintering stage. In the first sintering stage, the temperature is increased from room temperature to 180°C at a rate of 5°C / min, sintered for 1 hour, then increased from 180°C to 530°C at a rate of 5°C / min, sintered for 5.5 hours, and then cooled. In the second sintering stage, the temperature is increased from room temperature to 530°C at a rate of 5°C / min, sintered for 1.5 hours, then increased from 530°C to 770°C at a rate of 5°C / min, sintered for 5.5 hours, and then cooled from 770°C to room temperature at a rate of 5°C / min to obtain boron-doped lithium iron phosphate cathode material.
[0129] Comparative Example 1
[0130] This comparative example provides a lithium iron phosphate cathode material, specifically a lithium iron phosphate cathode material, prepared using the same method as in Example 7, except that:
[0131] No boron oxide was added in step (1);
[0132] Step (2) In the second sintering stage, the temperature is increased from room temperature to 500℃ at a heating rate of 5℃ / min and sintered for 1.5h. Then, the temperature is increased from 500℃ to 730℃ at a heating rate of 5℃ / min and sintered for 5.5h. Finally, the temperature is reduced from 730℃ to room temperature at a cooling rate of 5℃ / min.
[0133] Comparative Example 2
[0134] This comparative example provides a lithium iron phosphate cathode material, specifically a fluorine-doped lithium iron phosphate cathode material, and the preparation method includes:
[0135] (1) Dissolve ferric nitrate, ammonium dihydrogen phosphate, lithium carbonate, ammonium fluoride and glucose in water, mill, and spray dry to obtain solid precursor material;
[0136] (2) Sintering is carried out under a nitrogen atmosphere, specifically divided into a first sintering stage and a second sintering stage. In the first sintering stage, the solid precursor material is heated from room temperature to 400℃ at a heating rate of 5℃ / min and sintered for 3h. In the second sintering stage, the temperature is heated from 400℃ to 700℃ at a heating rate of 5℃ / min and sintered for 10h. Then, the temperature is cooled from 700℃ to room temperature at a cooling rate of 5℃ / min to obtain fluorine-doped lithium iron phosphate cathode material.
[0137] The positive electrode materials prepared in each embodiment and comparative example were used to fabricate coin cells. Specifically, the positive electrode materials prepared in each embodiment and comparative example were mixed uniformly with carbon black conductive agent, PVDF binder, and NMP solvent in a mass ratio of 95:2.5:2.5:5 to obtain a battery positive electrode slurry. The positive electrode slurry was coated on an aluminum foil with a thickness of 30 μm, and then vacuum dried and rolled to form a positive electrode sheet. A lithium metal sheet was used as the negative electrode, and the electrolyte consisted of 1.15 M LiPF6 and EC and DMC in a volume ratio of 1:1. A coin cell was then assembled.
[0138] Then, the electrochemical performance of the battery was tested, and the results are shown in Table 1. Simultaneously, SEM tests were performed on the lithium iron phosphate cathode materials prepared in Examples 1 and 3. Figure 1 The SEM image of Example 1 is given, and statistics are also presented. Figure 1 The particle size of each particle in the material is used to obtain the particle size distribution map of the lithium iron phosphate cathode material, as shown below. Figure 2 As shown. Figure 3 The SEM image of Example 3 is given, and statistics are also presented. Figure 3 The particle size of each particle in the material is used to obtain the particle size distribution map of the lithium iron phosphate cathode material, as shown below. Figure 4 As shown.
[0139] Table 1. Electrochemical performance test results of each embodiment and comparative example.
[0140]
[0141]
[0142] Figure 1 and Figure 2 The images show the SEM image and particle size distribution of the lithium iron phosphate cathode material prepared in Example 1. No polymer monomers were added during this preparation process. Figure 1 and Figure 2 As can be seen, the particles are small and aggregated in large quantities, with each primary particle measuring approximately 280 nm.
[0143] Figure 3 and Figure 4 The images show the SEM images and particle size distribution of the lithium iron phosphate cathode material prepared in Example 3. Figure 3 and Figure 4 It can be seen that the lithium iron phosphate cathode material prepared in Example 3 of this application has a relatively regular morphology, good sphericity, good particle dispersion, and the size of the particles shows a certain gradation effect, with the primary particles being approximately 300 nm.
[0144] As shown in Table 1, compared to Comparative Examples 1 and 2, the fluorine-doped lithium iron phosphate cathode material prepared in this application exhibits superior electrochemical performance and high rate capability. Fluorine ions favor specific oxygen sites in the crystal structure, enhancing the material's conductivity. Furthermore, the olivine structure of LiFePO4 is retained after doping, while lattice parameters and antisite defects are reduced, increasing the crystal size. The addition of a small amount of fluorine increases its conductivity from 4.6 × 10⁻⁶ to 4.6 × 10⁻⁶. -7 cm -1 Increased to 2.3×10 -6 cm -1 This has a positive impact on electrochemical performance, thereby increasing its conductivity and further enhancing its electrochemical performance.
[0145] The boron-doped lithium iron phosphate cathode material prepared in this application has a significantly higher compaction density than the undoped lithium iron phosphate cathode material, and also has a higher capacity and longer cycle life.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0147] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, any of the embodiments claimed above can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a lithium iron phosphate cathode material, characterized in that, include: Raw materials including iron, phosphorus, lithium and carbon sources are dissolved in a solvent, and after the solvent is evaporated, a precursor material is obtained. The precursor material is subjected to a first sintering and a second sintering to obtain the lithium iron phosphate cathode material. The lithium iron phosphate cathode material is doped with boron and fluorine; The raw materials also include a boron source; the boron source includes at least one of boron oxide, boron phosphate, trimethyl borate, triethyl borate, and tripropyl borate. The mass of the boron source does not exceed 5% of the theoretical yield of the lithium iron phosphate cathode material; The first sintering process includes: heating from room temperature to 100℃-380℃ in an inert gas atmosphere, holding at that temperature for 1h-1.5h, then further heating to 480℃-680℃, holding at that temperature for 4.5h-6.5h, and then cooling to room temperature; The second sintering process includes: heating from room temperature to 480℃-680℃ in an inert gas atmosphere, holding at that temperature for 1h-1.5h, then further heating to 680℃-810℃, holding at that temperature for 4.5h-8h, and then cooling to room temperature; The preparation method satisfies any one of the following schemes: Option 1: The carbon source is polyvinylidene fluoride (PVDF), and the mass of PVDF is 1%-20% of the theoretical yield of the lithium iron phosphate cathode material. Option 2: The carbon source includes at least one of glucose, sucrose, starch, citric acid, amino acids, and polyethylene glycol, and the mass of the carbon source is 1%-20% of the theoretical yield of the lithium iron phosphate cathode material; and before the first sintering, the fluorine source is dissolved in N-methyl-2-pyrrolidone, then added to the precursor material, mixed, and dried; the fluorine source is polyvinylidene fluoride, and the mass of the fluorine source is greater than 0 and not more than 10% of the theoretical yield of the lithium iron phosphate cathode material.
2. The preparation method according to claim 1, characterized in that, At least one of the following conditions must be met: a. The iron source includes at least one of ferrous oxalate, ferrous acetate, ferrous chloride, ferrous sulfate, ferric oxide, ferric phosphate, ferric nitrate, ferric chloride, ferric sulfate, ferric hydroxide, ferric citrate, and ferric acetate; b. The phosphorus source includes at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, iron phosphate, lithium phosphate, and lithium dihydrogen phosphate; c. The lithium source includes at least one of lithium hydroxide, lithium oxalate, lithium carbonate, lithium acetate, lithium phosphate, lithium dihydrogen phosphate, lithium hydrogen phosphate, lithium chloride, and lithium nitrate; d. The solvent includes at least one of water and hydrophilic organic solvents.
3. The preparation method according to claim 1, characterized in that, The molar ratio of iron, phosphorus, and lithium in the iron source, phosphorus source, and lithium source is (0.90-1.15):(0.95-1.15):(0.95-1.15).
4. The preparation method according to claim 1, characterized in that, The raw materials also include polymer monomers.
5. The preparation method according to claim 4, characterized in that, At least one of the following conditions must be met: e. The heating rates of the first sintering and the second sintering are each independently 1℃ / min-5℃ / min; f. The drying process includes: vacuum drying at 100℃-150℃; g. The polymer monomer includes at least one of styrene, propylene, acrylic acid, acrylate, acrylamide, acrylonitrile and their derivatives; h. The molar amount of the polymer monomer is 1.1%-220% of the molar amount of iron in the iron source.
6. The preparation method according to claim 4, characterized in that, When the raw material further comprises polymer monomers, dissolving the raw material in a solvent includes: The raw materials, including an iron source, a phosphorus source, a lithium source, and the polymer monomer, are dissolved in the solvent containing an oxidizing acid and / or a non-oxidizing acid to obtain a mixture. When the mixture contains the oxidizing acid, the carbon source is added to the mixture to allow the solvent to evaporate naturally and the polymer monomers to undergo a polymerization reaction to generate a polymer. When the mixture does not contain the oxidizing acid, the carbon source is added to the mixture, followed by the addition of hydrogen peroxide to allow the solvent to evaporate naturally and the polymer monomers to undergo a polymerization reaction to generate a polymer.
7. The preparation method according to claim 6, characterized in that, At least one of the following conditions must be met: i. The oxidizing acid includes at least one of nitric acid and sulfuric acid; j. The non-oxidizing acid includes at least one of hydrochloric acid, phosphoric acid, and acetic acid; k. The hydrogen ion concentration in the mixture is above 1 mol / L.
8. The preparation method according to any one of claims 1-7, characterized in that, Before performing the first and second sintering, the process further includes: refining the particle size of the precursor material.
9. A lithium iron phosphate cathode material, characterized in that, The lithium iron phosphate cathode material was prepared using the preparation method described in any one of claims 1-8.
10. A lithium-ion battery, characterized in that, Including the lithium iron phosphate cathode material as described in claim 9.
Citation Information
Patent Citations
Fluorinion-doped lithium iron phosphate material and preparation methods thereof
CN102024951A
Doping modified lithium iron phosphate material, preparation method thereof and lithium ion battery
CN116053467A
High-tap-density lithium iron phosphate positive electrode material as well as preparation method and application thereof
CN116565180A